Examining the Performance of Islamic Banks in the Context of Bangladesh - Siddiqua , Ayesha (Global Disclosure of Economics and Business, 2017)
As a unique banking system Islamic Banking gained popularity all over the world. In 1983 Bangladesh also came forward with Islamic banking. This study focused on the performance of six selected Islamic banks in Bangladesh during 2011-2015. Researchers collected data from the annual reports of the Banks. Variables such as investment, total asset, deposit, earnings per share (EPS), return on asset (ROA) and return on equity (ROE) were selected for the study. In this study the main tools were growth and trend analysis. This empirical investigation revealed that the growth of total asset, deposit and investment was up to the mark but the Banks were not able to increase the growth rate of EPS, ROA and ROE. The result also showed that Islamic banks are doing good job in Bangladesh although the Banks are operating according to the conventional banking framework.JEL Classification Code: G 21